STRATEGI MANAJEMEN KONFLIK SEBAGAI UPAYA PENINGKATAN MUTU LEMBAGA PENDIDIKAN ISLAM - Andi Tiara Nur Fadhillah; Sudadi; Bahrani (STKIP Subang, 2026)
This article examines conflict management strategies as an effort to improve the quality of Islamic educational institutions. Conflict is an inevitable phenomenon in every organization, including Islamic educational institutions that have complex institutional dynamics. Unmanaged conflict has the potential to hinder educational goal achievement, deteriorate work climate, and weaken service quality. Conversely, strategically and constructively managed conflict can serve as a catalyst for innovation, strengthen organizational cohesion, and drive continuous quality improvement. Using a library research approach with critical analysis of recent academic literature from Indonesian and international journals as well as foundational texts, this article examines: (1) the concept and typology of conflict in Islamic educational institutions; (2) relevant conflict management models and strategies; (3) the relationship between effective conflict management and institutional quality improvement; and (4) recommendations for implementing conflict management strategies in the Islamic education context. The findings indicate that integrative conflict management strategies—which combine collaborative approaches, Islamic value-based mediation, and transformational leadership—prove most effective in converting conflict from a barrier into positive energy for quality improvement in Islamic educational institutions.